Factors Influencing Impulsive Buying Behaviour of Women in Supermarkets of Nepal - KC, Ajita; Tamang, Puja (Journal of Business and Social Sciences Research, 2022)
The primary goal of this study is to examine the factors influencing Nepalese women’s impulsive buying behaviour in supermarkets. Cross-sectional research design was adopted for carrying out the study in which 211 responses were collected both online and in printed form. Selection of respondents was based on convenience and judgement sampling. Women’s impulsive purchasing behaviour in supermarkets was found to be highly influenced by their financial independence and the store environment. Further, the outcomes of the study reveal that women are more inclined to shop when they have the financial means to pay for their items by themselves, while the store environment influences women to adjust their inflexible shopping lists. So, supermarkets are advised to arrange the store with good ambience and friendly staffs. Future studies shall take a broader geographic perspective and factors like packaging, culture, and way of life into consideration.